Pre-qualification documents for pre-cast pile subcontractor - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the pre-qualification documents for pre-cast pile subcontractor of Brac University new campus development project .